2003
DOI: 10.1592/phco.23.15.1611.31962
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Review of the Relationship Between Microalbuminuria and Cardiovascular Events in Patients with Diabetes Mellitus and Hypertension

Abstract: From the limited information available, the risk of cardiovascular events and mortality is estimated to be 2-8 times higher when microalbuminuria is present in patients with diabetes and hypertension. Point estimates in relative risk of cardiovascular morbidity and mortality in patients with diabetes and hypertension were generally higher compared with studies estimating risk in those with only diabetes. Studies that examine the relationship between microalbuminuria (scaled as a continuous or ordinal variable)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…GFR was calculated by the Schwartz formula with less than 90ml / minute / 1.73 m 2 was classified as an abnormal value (10)(11)(12). Hypertension was defined as blood pressure higher than the 95th percentile for age and sex (9,10,13). Urine measurements at follow-up were made using first morning specimens.…”
Section: Methodsmentioning
confidence: 99%
“…GFR was calculated by the Schwartz formula with less than 90ml / minute / 1.73 m 2 was classified as an abnormal value (10)(11)(12). Hypertension was defined as blood pressure higher than the 95th percentile for age and sex (9,10,13). Urine measurements at follow-up were made using first morning specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Development of albuminuria in patients with diabetes is believed to increase the risk for cardiovascular events by two to eight times (35,36), through mechanisms that could involve low-grade inflammation, ED, and impaired insulin sensitivity (10,(37)(38)(39). Of note, a recent placebo-controlled study of patients with type 2 diabetes showed that insulin sensitizers (thiazolidinediones) not only decreased UAE but also enhanced insulin sensitivity and decreased circulating TNF-␣ levels (40).…”
Section: Ptx3 and Proteinuria In Patients With Type 2 Diabetesmentioning
confidence: 99%
“…Greater recent attention has been paid to describing this association in patients with type 2 diabetes [5,6,8,9,43]. A 10-year observational follow-up study of 939 adults with type 1 diabetes at the Steno Diabetes Centre showed that microalbuminuria predicted cardiovascular mortality independently of classical risk factors, with relative risk (95% confidence interval) of 1.45 (1.18-1.77) [3,4].…”
Section: Microalbuminuria Predicts Cardiovascular Events In Patients mentioning
confidence: 99%